Endoscopic endonasal transsphenoidal surgery for unusual sellar lesions: eight cases and review of the literature - Wu, Jiandong; Deng, Peng; Qian, Jinhong; Lu, Yanli; Ding, Zhiliang; Hu, Xiaolong; Gong, Yuhui; Tang, Xiaoyu; Ma, Mian (Frontiers in Neurology, 2024)
Background Preoperative imaging for some unusual lesions in the sellar region can pose challenges in establishing a definitive diagnosis, impacting treatment strategies. Methods This study is a retrospective analysis of eight cases involving unusual sellar region lesions, all treated with endoscopic endonasal transsphenoidal surgery (EETS). We present the clinical, endocrine, and radiological characteristics, along with the outcomes of these cases. Results Among the eight cases, the lesions were identified as follows: Solitary fibrous tumor (SFT) in one case, Lymphocytic hypophysitis (LYH) in one case, Cavernous sinus hemangiomas (CSH) in one case, Ossifying fibroma (OF) in two cases; Sphenoid sinus mucocele (SSM) in one case, Pituitary abscess (PA) in two cases. All patients underwent successful EETS, and their diagnoses were confirmed through pathological examination. Postoperatively, all patients had uneventful recoveries without occurrences of diabetes insipidus or visual impairment. Conclusion Our study retrospectively analyzed eight unusual lesions of the sellar region. Some lesions exhibit specific imaging characteristics and clinical details that can aid in preoperative diagnosis and inform treatment strategies for these unusual sellar diseases.